0.333333333333333x+0.333333333333333=0.4-0.666666666666667x+0.4

Simple and best practice solution for 0.333333333333333x+0.333333333333333=0.4-0.666666666666667x+0.4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution o

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.333333333333333x+0.333333333333333=0.4-0.666666666666667x+0.4 equation:


Simplifying
0.333333333333333x + 0.333333333333333 = 0.4 + -0.666666666666667x + 0.4

Reorder the terms:
0.333333333333333 + 0.333333333333333x = 0.4 + -0.666666666666667x + 0.4

Reorder the terms:
0.333333333333333 + 0.333333333333333x = 0.4 + 0.4 + -0.666666666666667x

Combine like terms: 0.4 + 0.4 = 0.8
0.333333333333333 + 0.333333333333333x = 0.8 + -0.666666666666667x

Solving
0.333333333333333 + 0.333333333333333x = 0.8 + -0.666666666666667x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.666666666666667x' to each side of the equation.
0.333333333333333 + 0.333333333333333x + 0.666666666666667x = 0.8 + -0.666666666666667x + 0.666666666666667x

Combine like terms: 0.333333333333333x + 0.666666666666667x = 1x
0.333333333333333 + 1x = 0.8 + -0.666666666666667x + 0.666666666666667x

Combine like terms: -0.666666666666667x + 0.666666666666667x = 0.000000000000000
0.333333333333333 + 1x = 0.8 + 0.000000000000000
0.333333333333333 + 1x = 0.8

Add '-0.333333333333333' to each side of the equation.
0.333333333333333 + -0.333333333333333 + 1x = 0.8 + -0.333333333333333

Combine like terms: 0.333333333333333 + -0.333333333333333 = 0.000000000000000
0.000000000000000 + 1x = 0.8 + -0.333333333333333
1x = 0.8 + -0.333333333333333

Combine like terms: 0.8 + -0.333333333333333 = 0.466666666666667
1x = 0.466666666666667

Divide each side by '1'.
x = 0.4666666667

Simplifying
x = 0.4666666667

See similar equations:

| 5x-8x+10x=28-10x+3 | | 10-2x=62 | | -3(2x+11)-22=-2(x+12)+9 | | 1x+3=2x+5 | | -5x-4(-7+13)=132 | | 9a^4-52a^2+64=0 | | 5x-3(2x+4)=-17 | | 2x+4(-2x+12)=6 | | 6x+2(5x+3)=134 | | 4+c=16 | | 4x+13x+9X= | | fg(2)= | | 1+x+3=15+x | | fg(x)= | | 5(x-1.3)=9.3 | | -8-2x=12-7x | | 0.2x=-10 | | 1.5r-5=.5r | | h-g(x)= | | 3x=2(20-x) | | 3x-4y=-1 | | 8+5x=44+1 | | 6x+7(-7x-12)=174 | | (16b-7)-5(3b+4)=-6 | | 2x-5(4x+12)=138 | | -3(8p+5)-2(5-23p)=3(5+7p) | | f+h(x)= | | -2(4b+1)+(9b-1)=0 | | 2(x-25)=3x | | 6x-3(7x-16)=-72 | | 2j-k=p-14 | | 2w+5+3=58 |

Equations solver categories